Hacking History: Redressing Gender Inequities on Wikipedia Through an Editathon - Hood, Nina; Littlejohn, Allison (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Editathons are a relatively new type of learning event, which enable participants to create or edit Wikipedia content on a particular topic. This paper explores the experiences of nine participants of an editathon at the University of Edinburgh on the topic of the Edinburgh Seven, who were the first women to attend medical school in 19th century United Kingdom. This study draws on the critical approach to learning technology to position and explore an editathon as a learning opportunity to increase participants’ critical awareness of how the Internet, open resources, and Wikipedia are shaping how we engage with information and construct knowledge. Within this, there is a particular focus on recognising persisting gender inequities and biases online. The qualitative interviews captured rich narrative learning stories, which traced the journey participants took during the editathon. Participants transformed from being online information consumers to active contributors (editors), prompting new critical understandings and an evolving sense of agency. The participants’ learning was focused in three primary areas: (1) a rewriting of history that redresses gender inequities and the championing of the female voice on Wikipedia (both as editors and subject matter); (2) the role of Wikipedia in shaping society’s access to and engagement with information, particularly information on traditionally marginalised subjects, and the interplay of the individual and the collective in developing and owning that knowledge; and (3) the positioning of traditional media in the digital age.